Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3389/fpubh.2021.578366
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological Impact of COVID-19 Among Pakistani Adults in Lahore

Abstract: Background: In the wake of the worldwide spread of the novel coronavirus and the resultant restrictive measures, mental health has become a crucial issue. Physical health is not the only aspect of humans that is at risk. Globally, the rates and severity of mental illness are being significantly impacted by this pandemic. Two scales have been validated to measure the impact of coronavirus disease 2019 (COVID-19) on the levels of anxiety and obsessional thinking in clinical and non-clinical populations. The pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 13 publications
(20 reference statements)
1
13
0
Order By: Relevance
“…The present results are also supported by another indigenous research conducted to measure the presence of COVID-19-related anxiety and OCD-related symptoms. Results indicated that men reported a high level of coronavirus-related anxiety and exhibited more OCD-like symptoms than women even though the research participants were more women (Majeed et al, 2021). Men's anxiety and depression could be related to the high prevalence of COVID-19 in them and its fatal nature.…”
Section: Resultsmentioning
confidence: 87%
“…The present results are also supported by another indigenous research conducted to measure the presence of COVID-19-related anxiety and OCD-related symptoms. Results indicated that men reported a high level of coronavirus-related anxiety and exhibited more OCD-like symptoms than women even though the research participants were more women (Majeed et al, 2021). Men's anxiety and depression could be related to the high prevalence of COVID-19 in them and its fatal nature.…”
Section: Resultsmentioning
confidence: 87%
“…These findings are parallel to a study conducted in a different city in Pakistan. They described that in comparison to other parts of the world, COVID-19 related anxiety issues are not much observed in this country [28].…”
Section: Discussionmentioning
confidence: 82%
“…When compared with the worldwide rate of 17.80% with major depression and 16.71% with distress, calculated under the same circumstances and time [COMET-G, ( 18 )], there was a higher rate of both in Canada. A low rate of increased anxiety during the pandemic was reported in Pakistan, and the authors concluded that it “demonstrates either the resilience of Pakistanis or the lack of understanding of the seriousness of the situation” ( 22 ). Higher distress levels were reported by Yael ( 23 ), who imagined the profile of individuals with elevated distress as: “being younger, female, not in a relationship, having a below-average income, being diagnosed with the disease, living alone during the outbreak, having a close other in a high-risk group, and negatively self-rating one’s health status.” Chang et al ( 24 ) found that fear of COVID-19 among people with mental illness was associated with psychological distress (including depression, anxiety, and stress), while the present study found that mental disorder is associated with depression only.…”
Section: Discussionmentioning
confidence: 99%